Automated tool to assess pair programming program quality - Omar, Mazni; Romli, Rohaida; Hussain, Azham (2008)
This paper aims to present an automated tool that has been developed to assess pair programming program quality.The tool known as Java Quality Measurement Tool or JaQMeT is used to assess specifically Java program quality.There are two program quality factors that can be assessed which are correctness and complexity. Pair programming program will be graded using JaQMeT. Then the results will be used to evaluate the effectiveness of pair programming.JaQMeT is only at its initial stage.It is an initial effort to facilitate the lecturers to reduce workload on grading programming assignment and specifically to assess pair programming program quality.Although JaQMeT has its several limitation but it is hoped that JaQMeT can be extended by using web-based technology and capable to check others program quality.